Object-relation data model (ORDM) for Malaysian biodiversity data. - Wahid, Mohd. Taib; Kamruzzaman, A. Z. M.; Mohamed Shariff, Abdul Rashid; Selamat, Harihodin (Penerbit UTM Press, 2005)

(untitled)
The economic importance and uses of the large number of biodiversity plant species of Malaysia make it essential for their biodiversity to be conserved. The complexity of natural history collection information and similar information within the scope of biodiversity informatics poses significant challenges for effective management of plant biodiversity data. In order to undertake the steps for biodiversity 'conservation such as identification of species, monitoring climate conditions, it is essential to efficiently manage the vast amount of biodiversity related data. This paper discusses about the object-relational conceptual design of biodiversity data model for long term stewardship of biodiversity information. A plenty of data models have been developed (such as BODHI, Oshadhi) which only support spatial data. In addition to this, most of the data models are relational model. The purpose of this research is to design a biodiversity data model that better facilitates the exploration and analysis of spatio-temporal biodiversity data by using object relational data model techniques. The goal of this study is to design a biodiversity model that is efficient for data management and able to integrate diverse set of spatio-temporal data that maybe required for analysis, and monitoring biodiversity data.